General-System Approach to the Development of Complex Activity Technology - Belov, Mikhail V.; Novikov, Dmitry A. (Procedia computer science, 2017)
The paper presents a uniform approach to general-system analysis of complex production activity (CPA). The formal description of CPA is based including the model of a structural element of activity and the structural models of CPA. The role of uncertainty in CPA and its technology development is discussed. A general-system algorithm of CPA technology development is described. It is demonstrated that the development of the CPA technology might be reduced to a). the description CPA in terms of structural models (at the general-system level); b).the development of industry-specific technologies for each of the elementary operations.